2021
DOI: 10.3390/ijms22126195
|View full text |Cite
|
Sign up to set email alerts
|

Improper Remodeling of Organelles Deputed to Ca2+ Handling and Aerobic ATP Production Underlies Muscle Dysfunction in Ageing

Abstract: Proper skeletal muscle function is controlled by intracellular Ca2+ concentration and by efficient production of energy (ATP), which, in turn, depend on: (a) the release and re-uptake of Ca2+ from sarcoplasmic-reticulum (SR) during excitation–contraction (EC) coupling, which controls the contraction and relaxation of sarcomeres; (b) the uptake of Ca2+ into the mitochondrial matrix, which stimulates aerobic ATP production; and finally (c) the entry of Ca2+ from the extracellular space via store-operated Ca2+ en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 285 publications
(423 reference statements)
0
12
0
Order By: Relevance
“…In this manuscript, we have taken advantage of the previous experience collected studying skeletal [40][41][42]54,55] and cardiac [8][9][10]34,59] muscle to study CRUs and mitochondria and their intracellular disposition, in ageing hearts from mice. The results presented in this manuscript show that ageing in cardiomyocytes causes the following:…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this manuscript, we have taken advantage of the previous experience collected studying skeletal [40][41][42]54,55] and cardiac [8][9][10]34,59] muscle to study CRUs and mitochondria and their intracellular disposition, in ageing hearts from mice. The results presented in this manuscript show that ageing in cardiomyocytes causes the following:…”
Section: Main Findingsmentioning
confidence: 99%
“…In physiological conditions, though, the synchronous activation of many sparks induced by depolarization, each of them arising from a different CRU, generates a homogeneous transient that leads to uniform activation of the contractile machinery [77][78][79]. However, the structural disruption of this system in ageing could result in improper activation of the contractile machinery [52][53][54].…”
Section: Eccoupling System Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the measurement of the plasma concentration of a large protein array, the authors identified a proteomic signature of muscle mitochondrial function assayed by phosphorous magnetic resonance spectroscopy [ 2 ]. The relevance of mitochondrial dysfunction to sarcopenia is further highlighted by the observation that alterations in intracellular calcium handling impact mitochondrial bioenergetics [ 3 ]. Muscle fiber denervation, an event involved in the pathogenesis of sarcopenia, induces damage of membrane structures involved in calcium handling and excitation–contraction coupling, and disruption of the mitochondrial network [ 3 ].…”
mentioning
confidence: 99%
“…The relevance of mitochondrial dysfunction to sarcopenia is further highlighted by the observation that alterations in intracellular calcium handling impact mitochondrial bioenergetics [ 3 ]. Muscle fiber denervation, an event involved in the pathogenesis of sarcopenia, induces damage of membrane structures involved in calcium handling and excitation–contraction coupling, and disruption of the mitochondrial network [ 3 ]. These alterations were also described in physically inactive old mice and were rescued by electrical stimulation regular exercise in both rodents and older persons [ 3 ].…”
mentioning
confidence: 99%